Resilienza: luci e ombre di un costrutto attuale - Fratini, Tommaso (Studi sulla Formazione/Open Journal of Education, 2014)
The article conducts a critical reading of the concept of resilience, discussing the implications for pedagogy. In the first part of the work, after reviewing the origins of the concept of resilience in evolutionary studies on risk and protection factors in the life cycle, the original psychoanalytic matrix is put into place, which extends the concept of coping and defense mechanisms. In the second part of the work, the pedagogical value of the concept of resilience is discussed within a critical view of adaptation and social change. This is expressed within a model of critical pedagogy already well defined and aimed at enhancing the significance of resistance against the social pathologies of our time, such as the basis of educational action in a particularly democratic and valuable sense.